Pengaruh Pengetahuan Kewirausahaan, Ekspektasi Pendapatan Dan Norma Subyektif Terhadap Minat Berwirausaha Melalui Media Online Pada Masa Pandemi Covid-19 Di FEBP Universitas Hindu Indonesia - Ni Putu Mira Kartini; Ni Komang Sumadi; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
Entrepreneurial activity has an essential role in strengthening the economy of a country, but not many people dare to be entrepreneurs since they are generally terrified of the danger of failure. To be able to increase entrepreneurs, first of all, it is vital to develop student enthusiasm in entrepreneurship. The goal of this study was to examine the effect of entrepreneurial expertise, income expectations, and subjective standards on entrepreneurial interest. The research was conducted at the UNHI campus on 1,202 FEBP students from the Management and Accounting Study Program who had attended entrepreneurship courses and by applying the Slovin Formula, a sample of 92 students was determined using the simple random sampling technique. Data gathering is done through interview and questionnaire method. The results of respondents' answers are then utilized to test the instrument by examining the validity and reliability of the instrument. Assumptions were tested using multiple linear regression analysis before hypotheses could be tested using multiple linear regression analysis and a series of traditional assumption tests. There was some evidence that entrepreneurial knowledge has a significant positive effect on entrepreneurial interest, income expectations have a significant positive effect on entrepreneurial interest, and subjective norms have a significant positive effect on entrepreneurial interest among FEBP UNHI students